SEJARAH MASUKNYA SUKU MANDAILING KE KABUPATEN ROKAN HULU TAHUN 1935-1945 - Andri '; Ridwan Melay; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Mandailing tribe is one of tribes located in Rokan Hulu Regency. Mandailing tribe in Rokan Hulu regency is an immigrant tribe from North Sumatera Province involved in civil war in Padang Galugur area to settle and live in Rokan Hulu District. The purpose of this research is 1) To know the history of entry of Mandailing tribe in Regency of Rokan Hulu Regency. 2) To know the factors inhibiting and pushing the entry of Mandailing tribe into Rokan Hulu District 3) To know the acceptance of local people to the entry of Mandailing tribe to Rokan Hulu regency 4) To know the role of government in the development of Mandailing tribe in Rokan Hulu regency. In this research using descriptive method, with qualitative approach, where it will provide complete information so that it is useful for science. The results of this study indicate that the Mandailing tribe is one part of the tribe that is in Rokan Hulu district. Who has long lived and lived in Rokan Hulu district from the days of the Kingdom of Rambah and Tambusai to the present time. And developed into one of the largest tribes in Rokan Hulu DistrictKeywords: Mandailing, Tribe